Menggali Pengaruh Dukungan Sosial terhadap Quarter Life Crisis pada Emerging Adulthood di Indonesia - Adlu, Khopidah; Mubina, Nuram; Leometa, Citra Hati (Universitas Muhammadiyah Metro, 2024)
Identity exploration in your 20s does not always go smoothly, but often experiences a developmental and emotional crisis called a quarter life crisis. The aim of this research is to determine the effect of social support on the quarter life crisis in emerging adulthood in Karawang. The methodology in this research is quantitative with an associative causality design. The population in this study were emerging adulthood individuals domiciled in Karawang, aged 18-25 years. The total number of research participants was 111 participants. The sampling technique uses non-probability sampling, namely convenience sampling technique. The instrument for measuring the quarter life crisis uses the Quarter life crisis (QLC) scale which was modified by researchers from the scale developed by Afandi et al., and an instrument to measure social support by adopting The Multidimensional Scale of Perceived Social Support (MSPSS) adapted by Sulistiani et al. The research results state that there is an influence of social support on the quarter life crisis in emerging adulthood in Karawang, with a value of sig. 0.002 < 0.05 which means Ha is accepted. Social support contributed 8.5% to the quarter life crisis in emerging adulthood in Karawang